The XIV Bakhtin Conference (ENTHYMEMA, 2011)
This is a short report of the XIV International Bakhtin Conference that took place in the Centro Residenziale Universitario of Bertinoro (Forlì-Cesena) from the 4th to the 8th of July, 2011, thanks to the organization of Federico Pellizzi and to the patronage of the Department of Filologia Classica e Italianistica of the University of Bologna, the Centro Studi sul Rinascimento and the Cassa di Risparimio di Bologna. The International conference, which usually takes place every two or three years, aims at investigating and presenting the most recent studies on Michail Bakhtin, but it also represents a chance for meeting scholars from different parts of the world and from different cultural and scholarly backgrounds.
Keywords: Michail Bachtin; International Bakhtin Conference; etica ed estetica; atto responsabile